2007
DOI: 10.1017/s1092852900026286
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Acutely Agitated and Psychotic Patient

Abstract: Agitation can present as an emergency in the course of numerous psychiatric conditions including intoxication, schizophrenia, bipolar disorder, and delirium. This article reviews relevant literature regarding the definition, etiology, measurement, and management of episodic agitation and pays particular attention to intramuscular treatments. The impact of changes in methodology between the era of first- and second-generation antipsychotics, the implications of those changes for external validity of studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 43 publications
2
28
0
1
Order By: Relevance
“…Treatment discontinuation, when necessary, occurred in most cases between 3 and 6 weeks from the initiation of oral therapy, when the eff ect of ziprasidone may have likely been already evident. We believe that the rapid eff ect of ziprasidone reported in the present study could be important in daily practice, as a fast improvement of clinical symptoms is a key goal in the management of the agitated patient [ 2 ] . Overall, our effi cacy results are in line with those of previous studies, which showed an improvement in symptoms following the sequential administration of IM and oral ziprasidone [ 12 , 15 ] .…”
Section: Discussion ▼mentioning
confidence: 70%
See 3 more Smart Citations
“…Treatment discontinuation, when necessary, occurred in most cases between 3 and 6 weeks from the initiation of oral therapy, when the eff ect of ziprasidone may have likely been already evident. We believe that the rapid eff ect of ziprasidone reported in the present study could be important in daily practice, as a fast improvement of clinical symptoms is a key goal in the management of the agitated patient [ 2 ] . Overall, our effi cacy results are in line with those of previous studies, which showed an improvement in symptoms following the sequential administration of IM and oral ziprasidone [ 12 , 15 ] .…”
Section: Discussion ▼mentioning
confidence: 70%
“…Ziprasidone was the fi rst atypical antipsychotic to be available in a rapid-acting IM formulation [ 6 ] , but the IM administration is now available for other drugs of the same class, e. g., olanzapine and aripiprazole [ 2 ] . Overall, the results of comparative studies have suggested an improved effi cacy for atypical antipsychotics in the treatment of acute exacerbation of schizophrenia, compared with conventional antipsychotics, even if further clinical experiences are advocated [ 2 ] . Additional evidence, possibly derived from robust studies, is also needed to provide new and more defi nite insights about the transition from IM to oral formulations of antipsychotics [ 3 ] .…”
Section: Discussion ▼mentioning
confidence: 99%
See 2 more Smart Citations
“…Ova terapija je posebno značajna kod učestalog treptanja i grčevitog zatvaranja očnih kapaka (blefarospazam) odraslih, jer pacijentu omogućava normalan vid. Blefarospazam se češće sreće kod odraslih pacijenata i nije specifičan za decu [13,14,15,16]. Mi nismo imali decu sa tim problemom.…”
unclassified